Modelling, simulation and fabrication of a hybrid solar dryer for the drying of medicinal and aromatic plant (MAPs)- case study Khyber Pakhtunkhwa (KPK), Pakistan - Mariam Mahmood (NUST201260740MCES64112F); Dr. Parvez Akhtar (USPCAS-E, NUST, Islamabad, 2014)
TH-16
Keywords: MS-ESE Thesis MS Thesis